Pengaruh ROE, ROA, EPS dan DER terhadap Harga Saham dengan PER sebagai Variabel Moderasi: Studi Empiris pada Perusahaan LQ-45 di Bursa Efek Indonesia - Amelia Prasetya; Halkadri Fitra (Universitas Negeri Padang, 2022)
The purpose of this research was to determine how the effect of financial ratios on stock prices. The renewal of this research where this study also aims to determine the role of PER in moderating the effect of ROE, ROA, EPS and DER on stock prices. This study uses the object of research in LQ-45 companies for than 2016-2020 period and obtains samples using the purposive sampling method as many as 21 companies. This research found that variables ROE, ROA, DER had no effect on stock prices with a significance value of 0.994, 0.935 and 0.514 which were greater than 0.05. But the results of this research state that EPS has an effect on stock prices with a significance value of 0. 000 which is less than 0.05. This study found that PER can moderate the relationship between EPS and stock prices with a significance value of 0.000 great we than 0.05 and positive direction, which means that PER can strengthen the relationship between EPS and stock prices. However, PER is not proven to moderate the relationship between ROE, ROA, EPS and DER to stock prices with a significance value of 0.180, 0.334 and 0.521 greater than 0.05. Recommendations for further research are expected to use other independent variables that are considered relevant to the research and use different data processing techniques such as Uji Moderasi Residual.